2007
DOI: 10.1097/01.pas.0000213335.40358.47
|View full text |Cite
|
Sign up to set email alerts
|

Intraepithelial Carcinoma of the Fimbria and Pelvic Serous Carcinoma: Evidence for a Causal Relationship

Abstract: Proposed origins of pelvic serous carcinoma include the ovary, fallopian tube, and peritoneum. Prophylactic salpingo-oophorectomies in BRCA+ women have recently identified the fimbria as a site of origin for early serous carcinoma (tubal intraepithelial carcinoma or TIC). We explored the relationship of TIC to pelvic serous carcinomas in consecutive cases with complete adnexal exam (SEE-FIM protocol). Cases positive (group A) or negative (group B) for endosalpinx (including fimbria) involvement, were subclassi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
801
4
15

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,003 publications
(839 citation statements)
references
References 30 publications
19
801
4
15
Order By: Relevance
“…Beginning in 2000, a progressive accumulation of data has implicated the distal fallopian tube as a site of origin of HGSC by identification of precursors in tubal epithelium [2][3][4][5]. As a consequence, in addition to clinical management guidelines recommending salpingo-oophorectomy for women with germ-line mutations in BRCA1 or BRCA2, recommendations have been published for opportunistic salpingectomy as a cancer preventive in women who are not at increased risk for ovarian cancer [9][10][11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Beginning in 2000, a progressive accumulation of data has implicated the distal fallopian tube as a site of origin of HGSC by identification of precursors in tubal epithelium [2][3][4][5]. As a consequence, in addition to clinical management guidelines recommending salpingo-oophorectomy for women with germ-line mutations in BRCA1 or BRCA2, recommendations have been published for opportunistic salpingectomy as a cancer preventive in women who are not at increased risk for ovarian cancer [9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Later that year, Cass and colleagues reported that most fallopian tube carcinomas arose in or near the fimbria [17]. Subsequently, Medeiros et al and Callahan et al reported that virtually all incidentally discovered HGSCs in RRSOs from women at genetic risk were found in the distal fallopian tube, and Kindelberger et al showed that over 40% of women with HGSC had evidence of STIC in their distal fallopian tube [3,12,18]. Thus, in our practice, the SEE-FIM protocol or a protocol in which the entire distal fallopian tube was submitted is followed in all salpingectomy specimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,40,41,47 Recent work proposes that epithelial ovarian cancer arises from three proposed origins, including the ovarian surface epithelium or mullerian inclusions, fallopian tube mucosa and mullerian epithelium elsewhere in the peritoneal cavity. 2,[48][49][50][51] Specifically, there is a growing body of evidence to suggest that both ovarian serous carcinoma and primary peritoneal carcinoma may arise from a precursor lesion in the distal tubal fimbria, [49][50][51] and thus both tumour types may be genetically related. Importantly, our results do not preclude a common site of origin; they probably reflect temporal 19 described DNA copy number alterations at all genomic loci for our selected microRNAs in ovarian serous carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…2 Efforts to identify the source of serous cancers have revealed that the oviduct, particularly the fimbriated end, is responsible for a larger proportion of serous cancers than previously thought, both in women with BRCA1 or BRCA2 mutations and the general population. [3][4][5][6][7] A serous cancer precursor has been proposed to arise in the distal oviduct. It may begin with TP53 mutations in secretory cells, leading to a clonally derived population with altered expression of p53 in the setting of DNA damage (H2AX).…”
mentioning
confidence: 99%